Easing Reentry by Supporting Fathers and Families. - Lindquist, Christine; McKay, Tasseli; McDonald, Hope Smiley; Herman-Stahl, Mindy; Bir, Anupa (Corrections Today, 2009)
This article examines programs offered to imprisoned fathers and their families under the Marriage and Family Strengthening Grants for Incarcerated Fathers and their Partners (MFS-IP) policy of the U.S. Department of Health and Human Services (HHS). It remarks on the challenges posed by the rehabilitation and reintegration of imprisoned fathers. Topics discussed include family support, family economic stability, and recidivism.